Deep and Ultra-deep oil/gas-source correlation methods: A review. Issue 1 (November 2020) - Wu, Yingqin; Wang, Zhiyu; Yuan, Longmiao
Abstract: With the deepening of oil and gas exploration practice, the increasing degree of oil and gas exploration and the increasing demand for oil and gas, the target of oil and gas exploration is gradually transformed into deep and ultra-deep areas. Meanwhile, the genesis of deep and ultra-deep reservoirs has gradually become the focus of research by domestic and foreign scholars. Oil/gas source correlation is an important means to study the genetic relationship between oil and gas and source rocks. Based on the geological and geochemical data, this paper summarizes and analyzes the advantages and disadvantages of the current methods of deep and ultra-deep oil/gas source correlation, and puts forward the existing problems and future development direction of deep and ultra-deep oil/gas source correlation.